Effect of Flipped Classroom Strategy on Achievement of the seventh grade students in mathematics in Nablus Governorate - Wahdan, Sabreen Wajeeh; Affouneh, Saida (Journal of Educational and Psychological Sciences, 2022)
The study aimed at investigating the effect of using the Flipped Classroom Strategy on seventh grade's achievement in the mathematics in Nablus Governorate; To check research questions and hypotheses, the researcher used the experimental approach with Quasi Experimental design. The study was applied to a sample of (79) students from the basic seventh grade of the Samir Abdi Al-Hady school, who were divided into two groups: one is experimental, composed of (40) students taught by the Engineering and Measurement Unit by the flipped classroom Strategy, and the other is a control group, with (39) students taught the same unit content in the traditional method, and the research tools consisted of a achievement test applied pre and post to the experimental and control groups, and the results indicated that the effect of the flipped classroom strategy was revealed in achievement grade 7 students in mathematics for the experimental group that was taught using the flipped classroom strategy, the researcher recommended a set of recommendations, including: Adopt a flipped classroom strategy that is inverted by teachers, mentors, and curriculum development officials, and create maths videos that take advantage of the technology's benefits ,that its effectiveness in raising school achievement.
Keywords: Flipped classroom; achievement; mathematics; seventh grade students